KONTRIBUSI FISIOLOGI OLAHRAGA DALAM MENGATASI RISIKO MENUJU PRESTASI OPTIMAL - Agus Parman; Tri Bayu Norito; Boy Indrayana; Muhammad Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Maximum achievement in the world of sports can only be achieved if training is carried out in a quality manner and follows systematic coaching principles such as the concept of coaching pyramid. The use of science and technology (IPTEK) is very important to obtain data on the physiological characteristics of athletes, which are then used as a reference in compiling training programs. In the training process, load management must consider the physical condition of each athlete, because the training load functions to stimulate an increase in their physiological capacity. However, errors in managing the training load can have a negative impact on the athlete's physical condition. Signs such as increased heart rate, frequent dizziness, and digestive and metabolic disorders are symptoms of overtraining that will hinder the athlete's performance in achieving the best performance. This overtraining is usually caused by errors in planning and implementing the training program